Ubud: Benteng Terbuka - Graeme MacRae (Universitas Udayana, 2014)
This article discusses evolution and present problemsof Ubud as a tourist town in the context of Bali tourismdevelopment. Ubud has always provided an alternativevision of what tourism in Bali could be. The metaphor of anOpen Fortress provides a useful lens for looking at Ubudover the past century. “Tourism” is in Ubud has alwaysbeen closely linked to an expatriate community and otherinternational economic activities. Tourism is not a onewayprocess – it is always a dialectical process betweenlocal communities and visitors (as Michel Picard told uslong ago). This process is always changing and in Ubud ithas now entered a new phase – involving a tourism/expatnexus that is quite disconnected from local community andculture.